2020
DOI: 10.1101/2020.06.09.20076646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prolonged SARS-CoV-2 Viral Shedding in Patients with COVID-19 was Associated with Delayed Initiation of Arbidol Treatment: a retrospective cohort study

Abstract: Objectives: Evaluate the risk factors of prolonged SARS-CoV-2 virus shedding and the impact of arbidol treatment on SARS-CoV-2 virus shedding. Methods: Data were retrospective collected from adults hospitalized with COVID-19 in Wuhan Union Hospital. We described the clinical features and SARS-CoV-2 RNA shedding of patients with COVID-19 and evaluated factors associated with prolonged virus shedding by multivariate regression analysis. Results: Among 238 patients, the median age was 55.5 years, 57.1% were fema… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…On multivariate analysis, old age, malignancy, steroid use, and concomitant pneumonia were identified as risk factors for prolonged viral shedding in this study, consistent with previous studies ( Fu et al, 2020 , Yan et al, 2020a , Yan et al, 2020b , Zhou et al, 2020 ). Old age, comorbidities, and steroid use might blunt the host immune response, thereby promoting viral replication.…”
Section: Discussionsupporting
confidence: 91%
“…On multivariate analysis, old age, malignancy, steroid use, and concomitant pneumonia were identified as risk factors for prolonged viral shedding in this study, consistent with previous studies ( Fu et al, 2020 , Yan et al, 2020a , Yan et al, 2020b , Zhou et al, 2020 ). Old age, comorbidities, and steroid use might blunt the host immune response, thereby promoting viral replication.…”
Section: Discussionsupporting
confidence: 91%
“…Although this study presents evidence of JAK-inhibitors and Type I interferon therapies for COVID-19 patients, the evaluated studies included conflicting results; Giudice et al reported a positive association between JAK-inhibitor therapy and the odds of mortality, [27] while the other studies analyzed and the summary statistic calculated demonstrated a negative association between JAK-inhibitor intervention and mortality (23,24,26). In addition, two studies consistently demonstrated opposite associations between Type I interferon therapy and clinical outcomes, [30,33] when comparing summary statistics and other included studies. [28,29,31,34,35] Heterogeneity among populations studied may play a role in the disparate individual results, as half of these studies were conducted in China, one was conducted in Iran, five were conducted in Western Europe, and one was conducted in Cuba.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al showed in a retrospective observational study that 16 COVID-19 patients treated with umifenovir plus lopinavir/ritonavir combination had more favorable viral clearance and chest CT findings compared to lopinavir/ ritonavir monotherapy (Deng et al, 2020). A retrospective study demonstrated that early administration of umifenovir or umifenovir in combination IFN significantly shortened the duration of viral shedding in COVID-19 patients (Zhou Y. et al, 2020). Furthermore, a limited retrospective cohort study reported that umifenovir tends to improve the discharging rate and reduce mortality rate (Wang et al, 2020b).…”
Section: Drugs With Mixed Modes Of Actionmentioning
confidence: 99%